Deficient mismatch repair as a prognostic marker in stage II colon cancer patients - Gkekas, Ioannis; Novotny, Jan; Fabian, Pavel; Nemecek, Radim; Palmqvist, Richard; Strigård, Karin; Pecen, Ladislav; Svoboda, Tomas; Gurlich, Robert; Gunnarsson, Ulf (European journal of surgical oncology, 2019)
BACKGROUND: A number of reports have evaluated the relationship between deficient DNA mismatch repair (dMMR) and colorectal cancer prognosis. Unfortunately, the exact prognostic role of dMMR has not been clearly established due to contradictory results. This study aims to determine the prognostic impact of dMRR in stage II colon cancer patients only. The appropriate identification of high-risk stage II colon cancers is of paramount importance in the selection of patients who may benefit from adjuvant treatment after surgery. METHODS: Four hundred and fifty-two patients with curative resection of stage II colon cancer were included. Hospital records were used as data source, providing clinical, surgical, pathology, oncology and follow-up information for statistical analysis focusing on overall survival (OS) and time to progression (TTP). Mismatch repair status was determined by immunohistochemistry. Patient survival was followed-up for a mean of 77·35 months. RESULTS: dMMR was detected in 93 of 452 patients (20·6%). No impact on overall survival (Log-Rank, p = 0·583, 95% CI 0·76-1·67). However, the hazard ratio 0·50 for TTP was highly significant (Log-Rank, p = 0·012, 95% CI 0·28-0·87) in patients with dMMR compared with those with mismatch repair proficient tumours (pMMR). CONCLUSIONS: Patients with dMMR tumours have a lower risk for recurrence compared to those with pMMR tumours, but this finding did not correlate to better overall survival.
Keywords: senioři; DNA, Neoplasm; senioři nad 80 let; Retrospective Studies; Stage II; Prognosis; Colon cancer; dMMR; imunohistochemie; Middle Aged; mužské pohlaví; adenokarcinom; oprava chybného párování bází DNA; Adult; kombinovaná terapie; Follow-Up Studies; následné studie; Aged, 80 and over; nádory tračníku; Immunohistochemistry; Neoplasm Staging; Prognostic factors; ženské pohlaví; prognóza; DNA Mismatch Repair; retrospektivní studie; Humans; Colonic Neoplasms; DNA nádorová; lidé středního věku; Combined Modality Therapy; staging nádorů; dospělí; Female; Aged; Adenocarcinoma; lidé; Male